Tindak Pidana Penipuan Penerimaan Pegawai Negeri Sipil di Denpasar - Livia Kusomo; Anak Agung Sagung Laksmi Dewi; I Wayan Arthanaya (Jurnal Analogi Hukum, 2020)
Abstract—Crime of CPNS fraud is common in both remote and urban areas. This is due to the large number of people who think that work as a civil servant is a safe and secure job. The discussion of this paper includes; What are the factors that lead to criminal acts of fraud from the point of view of law and society, how are sanctions and responsibilities of perpetrators of criminal acts of fraud CPNS. This research is normative research. Legal materials obtained from from the Warmadewa University Faculty of Law Library and the Krisna Law Office Library. Factors influencing fraudulent acts are lack of burden of sanctions or lack of commensurate penalties and poverty factors. Case studies in this paper are taken from the decisions of the Denpasar District Court (Decision Number: 382 / PID.B / 2018 / PN DPS); perpetrators of criminal offenses of CPNS that were enforced article 378 of the Criminal Code concerning fraudulent crimes with sanctions of a maximum of four (4) years in prison. This type of fraud can damage the character and morals of the nation, so the government should pay more attention to it and for the perpetrators to be given appropriate punishment in order to get a deterrent effect. The community is also expected to help law enforcement officials by reporting it if they know that this action was carried out and that law enforcement officers should provide protection for informer.